2014
DOI: 10.3389/fnhum.2014.00657
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hemispheric dominance for receptive language in pediatric patients under sedation using magnetoencephalography

Abstract: Non-invasive assessment of hemispheric dominance for receptive language using magnetoencephalography (MEG) is now a well-established procedure used across several epilepsy centers in the context of pre-surgical evaluation of children and adults while awake, alert and attentive. However, the utility of MEG for the same purpose, in cases of sedated patients, is contested. Establishment of the efficiency of MEG is especially important in the case of children who, for a number of reasons, must be assessed under se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
(43 reference statements)
0
13
1
1
Order By: Relevance
“…Yet despite the overall positive contribution of MEG in the assessment of language localization in typically developing individuals, data on its clinical use in clinical pediatric populations is still relatively modest. Recent studies have reported the feasibility of passive paradigms in children and adolescents under sedation (Rezaie et al 2014 ) and during sleep (Van Poppel et al 2012 ), but MEG studies using more traditional expressive language tasks in pre-surgical assessment of children are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Yet despite the overall positive contribution of MEG in the assessment of language localization in typically developing individuals, data on its clinical use in clinical pediatric populations is still relatively modest. Recent studies have reported the feasibility of passive paradigms in children and adolescents under sedation (Rezaie et al 2014 ) and during sleep (Van Poppel et al 2012 ), but MEG studies using more traditional expressive language tasks in pre-surgical assessment of children are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Использование МЭГ для неинвазивной оценки доминирующего полушария в восприятии речи является хорошо отработанной процедурой при лечении эпилепсии у детей и взрослых хирургическим способом. Авторы работы говорят о важности оценки функционирования мозга, определении доминирующего полушария у детей, которых необходимо поддерживать седативной терапией в дооперационном периоде [21]. Для определения доминирующего полушария восприятия речи необходимо понять, достаточно ли активируются корковые механизмы лингвистической обработки речевых стимулов при седатации.…”
Section: спектральные и пространственные характеристики речевой активunclassified
“…In young children and cognitively impaired patients, this may not be feasible for the patients. Interestingly, successful passive MEG language mapping in small groups of sleeping or sedated children have been reported [70,88]. For example, one Meg study used a word listening paradigm in 3 children in natural or propofol-induced sleep and successfully lateralized the receptive language areas [88].…”
Section: Preoperative Mapping Of Verbal Language Functionmentioning
confidence: 99%